Mitigating biomass recalcitrance for plant‐based bioenergy production - Vincent Ninkuu; Zhixin Liu; Yaping Zhou; Enzhi Guo; Xiao Song; Peibo Gao; Yajia Xie; Xuwu Sun (Modern Agriculture)
Abstract The emission of greenhouse gases, particularly carbon dioxide, predominantly from fossil fuel combustion has received critical warnings several times as their levels exceed the tolerable limits in view of global warming. This calls for a paradigm shift from a fossil fuel‐based source to a less hazardous bioenergy source. Plant feedstock is an attractive source of raw materials for bioenergy production; however, chemical or enzymatic digestion of the feedstock is expensive owing to the supramolecular lignocellulosic barrier, indicating the need for better alternatives. Several attempts have been made towards reducing the biomass recalcitrance of straw using genetic transformations. We present a review highlighting potential plant candidates for bioenergy production, the lignocellulose composition of the feedstock, how the composition can impede enzymatic degradation, the regulation of lignocellulose polymer biosynthesis, and the influence of genetic transformation on biomass saccharification. Moreover, the review also discusses conflicting research interests in biomass recalcitrance and suggests a common ground. The review findings suggest that bioenergy production from crop straws will drastically reduce over‐dependence on fossil fuels and consequently pollution levels.